2016
DOI: 10.1038/onc.2016.225
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic stress: obstacles and opportunities for innovative immunotherapy of cancer

Abstract: Tumors use several strategies to evade the host immune response, including creation of an immune-suppressive and hostile tumor environment. Tissue hypoxia due to inadequate blood supply is reported to develop very early during tumor establishment. Hypoxic stress has a strong impact on tumor cell biology. In particular, tissue hypoxia contributes to therapeutic resistance, heterogeneity and progression. It also interferes with immune plasticity, promotes the differentiation and expansion of immune-suppressive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
245
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(246 citation statements)
references
References 100 publications
1
245
0
Order By: Relevance
“…Even if hypoxia does not impact directly CTL cytolytic capacities, seminal studies from Chouaib et al. have shown that hypoxia induces resistance of tumor cells to CTL-mediated cytotoxicity, as recently reviewed 12 . Indeed, hypoxia promotes autophagy in tumor cells through a mechanism involving STAT3 activation and miR-210 upregulation, leading to selective degradation of granzyme B 53-56 .…”
Section: Hypoxia and Reactivation Of Cd8+ T Cellsmentioning
confidence: 95%
“…Even if hypoxia does not impact directly CTL cytolytic capacities, seminal studies from Chouaib et al. have shown that hypoxia induces resistance of tumor cells to CTL-mediated cytotoxicity, as recently reviewed 12 . Indeed, hypoxia promotes autophagy in tumor cells through a mechanism involving STAT3 activation and miR-210 upregulation, leading to selective degradation of granzyme B 53-56 .…”
Section: Hypoxia and Reactivation Of Cd8+ T Cellsmentioning
confidence: 95%
“…Hypoxia (decreased oxygen partial pressure from <0.1 mmHg (anoxia) to 15 mmHg) is a key microenviromental factor underlying malignant transformation, tumor heterogeneity, disease progression, immune escape, and therapy resistance [14]. In solid tumours, the uncontrolled proliferation of cancer cells combined with the structural abnormalities of the tumor vascular network results in the delivery of suboptimal concentrations of oxygen and other nutrients to cancer cells, creating hypoxic microregions [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia likely also supports immune resistance in tumors by supporting development of suppressive myeloid and T cell populations, by activating immunosuppressive signaling pathways in the tumor and stroma, and by creating a metabolically hostile environment for immune effector cells (17). …”
Section: Introductionmentioning
confidence: 99%